The role of Public Service Motivation and Organizational Culture for Organizational Commitment - Austen Agata; Zacny Bogna (Management, 2015)
The aim of the our paper is to discuss the relationships between organizational culture, Public Service Motivation (PSM) and organizational commitment (OC). On the basis of literature review we formulated hypotheses presenting potential relationships between mentioned constructs. We propose that there is a mutual influence between PSM and organizational culture and that organizational culture moderates the influence of Public Service Motivation on organizational commitment. Due to the presence of variables on different levels of analysis, we also discuss some issues of multilevel approach.